1978
DOI: 10.1007/bf00670846
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of androgenetic symptomatology with cyproterone acetate and ethinyl estradiol

Abstract: The effectiveness of therapy with cyproterone acetate and ethinyl estradiol was studied in 103 women. Acne and seborrhea responded best with 91.7 and 93.3% respectively, including complete and partial therapeutic success. For hirsutism complete remission and partial improvement were found in 75.3% of the treated women. Under therapy, body weight did not change in 51.9%, while 24.7% of the patients gained weight and 23.4% lost weight. The cycle length remained normal after therapy in 35.8%. Normalization or imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Also, these favorable structural changes continued to be present to some extent after the pill cessation. In addition, it was demonstrated that in some of those women, pattern and function of menstrual cycle improved after the treatment (Table 2 and Table 3) (10, 11). …”
Section: Symptoms Of Androgenisation (Seborrhea Acne Hirsutism mentioning
confidence: 97%
See 1 more Smart Citation
“…Also, these favorable structural changes continued to be present to some extent after the pill cessation. In addition, it was demonstrated that in some of those women, pattern and function of menstrual cycle improved after the treatment (Table 2 and Table 3) (10, 11). …”
Section: Symptoms Of Androgenisation (Seborrhea Acne Hirsutism mentioning
confidence: 97%
“…Intake before pregnancy has additional benefits (36). No difference is seen in risk reduction with different formulations of combined oral hormonal contraceptives including low dose pills (11, 37). The risk in four main histological types of epithelial ovarian cancer (serous, endometroid, mucinous, clear cell) are similarly reduced by the use of combined oral hormonal contraceptives, but not in germ cell ovarian malignancies (12).…”
Section: Prevention Of Ovarian Cancermentioning
confidence: 99%
“…Although our evaluation of the therapeutical results is not strictly quantitative, the percentage of positive results (94% for acne and 85% for hirsutism) is comparable with the results already reported [Hammerstein et al, 1975;Nan/i et al, 1975;Floersheim and Keller, 1976;Dewhurst etal., 1977;Steyer and Schmidt-Elmendorff, 1977;Schindler et al, 1978]. The treatment was slightly more effective in acne than in hirsutism.…”
Section: Discussionmentioning
confidence: 86%
“…The dose of CPA in the low-dosed combined preparation is insufficient in patients with severe androgenization. However, a treatment regimen first de-veloped by Hammerstein and Cupceancu (1969) and later modified slightly (Figure 22) -the reverse sequential scheme -has proved successful in large numbers of patients (Belisle and Love, 1986;Anderson, 1978;Breckwoldt et al, 1978;Carol et al;Dewhurst et al, 1977;Ekoe et al, 1980;Fraser et al;Frey and Aakvaag, 1981;Garner et al, 1984;Hammerstein, 1980Hammerstein, , 1987Holdaway et al, 1985;Jones et al, 1981;Molinatii et al, 1983;Moltz et al, 1980Moltz et al, , 1981Moltz et al, , 1982Sawers et al, 1982;Schindler, 1987;Schindler et al, 1978).…”
Section: Treatment Of Pcodmentioning
confidence: 99%